2020
DOI: 10.1515/cclm-2020-0737
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of acetylsalicylic acid and clopidogrel non-responsiveness assessed by light transmittance aggregometry and PFA-100® in patients undergoing neuroendovascular procedures

Abstract: ObjectivesDual platelet inhibition is commonly used for prevention of cardiovascular events in patients undergoing neuroendovascular procedures. Non-responsiveness to platelet inhibitors may be associated with adverse outcomes. The aim of this study was to evaluate the reliability of the platelet function analyzer PFA-100® in comparison to light transmittance aggregometry (LTA) for monitoring clopidogrel and acetylsalicylic acid (ASA) non-responsiveness in a cohort of patients treated for intracranial aneurysm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In a meta-analysis of 42 studies, Hovens et al reported a weighted mean prevalence of laboratory-defined aspirin resistance of 24% (range = 0–57%) with an inter-study heterogeneity ( I 2 ) of 94% [ 85 ]. Most included studies used one of three PFTs to define aspirin non-response, the choice of which strongly influenced estimates, consistent with studies that have demonstrated poor agreement between PFTs [ 87 , 88 ]. While this limits the practical applications of PFTs, they still provide reasonable evidence for aspirin resistance.…”
Section: Aspirinmentioning
confidence: 63%
“…In a meta-analysis of 42 studies, Hovens et al reported a weighted mean prevalence of laboratory-defined aspirin resistance of 24% (range = 0–57%) with an inter-study heterogeneity ( I 2 ) of 94% [ 85 ]. Most included studies used one of three PFTs to define aspirin non-response, the choice of which strongly influenced estimates, consistent with studies that have demonstrated poor agreement between PFTs [ 87 , 88 ]. While this limits the practical applications of PFTs, they still provide reasonable evidence for aspirin resistance.…”
Section: Aspirinmentioning
confidence: 63%
“…For comparison, some CT NRRs reported in the contemporary 6,16–29 and original literature 30–53 are shown in Figure 3. In most instances, these NRRs differ from each other and also from the manufacturer ranges, especially for C/ADP.…”
Section: Resultsmentioning
confidence: 99%
“…The Siemens product information CT NRRs are shown by the green horizontal dashed lines. Figure A shows NRRs from some contemporary literature as obtained from the recent literature search (see Methods), and reflecting information from the past 3 years 6,16–29 . Figure B shows NRRs from some early literature as otherwise reviewed in Reference 10 30–53 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation